“Straw in the Clay Soil” Strategy: Anticarbon Corrosive Fluorine‐Decorated Graphene Nanoribbons@CNT Composite for Long‐Term PEMFC - Song Jin; JunHwa Kwon; Jong Min Lee; Ye‐Rim Kim; Justin Georg Albers; Young‐Woo Choi; Sung Mook Choi; KwangSup Eom; Min Ho Seo (Advanced Science)
Abstract Carbon corrosion poses a significant challenge in polymer electrolyte membrane fuel cells (PEMFCs), leading to reduced cell performance due to catalyst layer degradation and catalyst detachment from electrodes. A promising approach to address this issue involves incorporating an anticorrosive carbon material into the oxygen reduction reaction (ORR) electrode, even in small quantities (≈3 wt% in electrode). Herein, the successful synthesis of fluorine‐doped graphene nanoribbons (F‐GNR) incorporated with graphitic carbon nanotubes (F‐GNR@CNT), demonstrating robust resistance to carbon corrosion is reported. By controlling the synthesis conditions using an exfoliation method, the properties of the composite are tailored. Electronic structural studies, employing density functional theory (DFT) calculations, to elucidate the roles of fluorine dopants and graphitic carbon nanotubes (CNTs) in mitigating carbon corrosion are conducted. Physicochemical and electrochemical characterization of F‐GNR@CNT reveal its effectiveness as a cathode additive at the single‐cell scale. The addition of F‐GNR@CNT to the Pt/C cathode improves durability by enhancing carbon corrosion resistance and water management, thus mitigating the flooding effect through tailored surface properties. Furthermore, advanced impedance analysis using a transmission line model is performed to gain insights into the internal resistance and capacitive properties of electrode structure.